PERKIRAAN JUMLAH PENDUDUK OPTIMAL DAMPAK ADANYA PERGURUAN TINGGI BARU DI KABUPATEN PEKALONGAN - Hariwibawa, Arga Prinandiga (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) ITERA, 2023)
The existence of the attraction zone in the form of infrastructure facilities and infrastructure supporting community activities is a special attraction for the community to build a residence in Pekalongan Regency. This triggered the population growth of Kajen District, which continued to peak; in the 2020–2022 range, there was an increase in the population of more than 75,000 people. The results of the analysis stated that the area of ​​Pekalongan Regency which covers 83,615 ha, as much as 52% of the area is a cultivation area. The remaining 35% is a buffer area, and 14% of it is an area with a protected function. This article is intended to estimate the maximum population that can be accommodated in Pekalongan Regency due to the existence of a new university, so that it will not have a negative impact on the environment . Meanwhile, to estimate this, data analysis methods are used by utilizing tools in the form of GIS and land carrying capacity calculations based on the determination guidelines carriage capacity and capacity environment. In accordance with the analysis of the carrying capacity of residential land functions in Pekalongan Regency, it was found that it currently has a DDPm value of 16.96. This represents that Pekalongan Regency is still very capable of supporting population growth.